The effect of job characteristics on intrinsic and extrinsic job satisfaction: the moderating role of psychological capital - García, David Montesa (2019)
This paper analyzes the differential effects of autonomy, skill variety, work significance, feedback from the job, and information processing on intrinsic and extrinsic job satisfaction, and the moderating role of psychological capital (PsyCap) in these relationships. The influence of job characteristics on job satisfaction has been well established in previous research, but the distinction between intrinsic and extrinsic satisfaction has hardly been considered. Moreover, their effects also depend on workers’ characteristics. PsyCap is a set of resources (self-efficacy, optimism, hope, and resilience) that could strengthen the positive effects of job characteristics and provide protection from negative ones. Hierarchical regressions analyzed data from 1647 workers in Spanish organizations. Results showed positive relationships between autonomy and feedback from the job and the two satisfaction dimensions, whereas significance and information processing were negatively related to extrinsic satisfaction. Moreover, PsyCap strengthens the positive effect of information processing and autonomy on intrinsic satisfaction, and it weakens the negative effect of information processing on extrinsic satisfaction. However, it also increases the negative effect of significance on extrinsic satisfaction. Therefore, job enrichment would be beneficial for intrinsic satisfaction, especially for people with high PsyCap, but it could be negative for extrinsic satisfaction.